An empirical analysis of macroeconomic factors and the effects on insurance demand and profitability - Napier, Hugh Robert Lennox (My University, 2015)
In any business it is critical to understand the key drivers of sales, costs and sustainability. This study aimed to understand whether macroeconomic indicators could be used to explain and predict insurance sales, cancellations and overall underwriting profitability in South Africa, and whether the drivers for insurance demand and profitability differed based on individual wealth. The significance of answering these questions is directly related to managing and running an insurance business in terms of which products to sell, and which consumer segments to target based on prevailing macroeconomic conditions. Regression analyses using Ordinary Least Squares were completed on both low income and high income consumer groups. Predictive models for sales (low income and high income groups) and profitability (low income group) were derived; however no model sufficiently explained cancellations in either income group. The explanatory variables for sales in the low and high income groups differed, suggesting that macroeconomic factors differentially influence buying behaviours in these groups. Sales and profitability in the low income group were explained by the same macroeconomic factors.
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2015.